Kuasa Kata Di Media Sosial dalam Paradigma Pemberitaan Kompas dan Tempo - Djony Herfan; Nurul Intan Pratiwi; Ade Haryani (Jurnalistik dan Media, 2024)
This research focuses on the issue of the power of words in media. The problem is the intertwined reporting between social media and mainstream media. The purpose of the study is to achieve the power of words in the accuracy of news. Words are intertwined in the news for language editors both in the Kompas and Tempo media. In general, the use of words on social media uses mixed language. The confusion of the use of words is reflected in the confusion of meaning. The meaning of words through social media is also intertwined with the use of foreign language words (English), alay, slang, and "Jaksel language". Therefore, language editors require word checking. Mainstream media editors devoutly curate words. For this reason, efforts are needed to accurately report the media. Several words were curated. Efforts to curate media coverage to achieve the accuracy of word meaning. So, every word curated in media coverage has precision, thoroughness, and precision. However, word curation attaches importance to the awareness, knowledge, and skills of language editors. This research reveals that significant word confusion in media reporting is curated based on a journalism approach. Thus, the confusion of the meaning of words disseminated through media coverage has accuracy. So, how connected words are is important to know their accuracy through meaning journalism. As one of the predictors of word incorrectness, it not only needs to be curated by language editors but also curated through documentation and literature studies. The reporting of Kompas and Tempo through some curated words is the essence of meaning journalism that can produce words with a meaning journalism approach.Keywords: Journalism Meaning, News, Journalistic Language